A UV tunable diode laser source based on an external resonant cavity for OH absorption detection - Gibb, J; Hancock, G; Kasyutich, V; Ritchie, G (2001)
A Solid-state tunable light source operating at 309-320 nm has been developed based on frequency up conversion of a cooled diode laser. Frequency doubling is achieved with a beta barium borate crystal enclosed in an external bow-tie cavity. The radiation produced is used for absorption detection of hydroxyl radicals generated by microwave discharge. The ultraviolet beam can be scanned 20-30 GHz by tuning the length of the doubling cavity using a piezoelectric transducer on one of the mirrors and locking the diode laser to the bow-tie cavity. Possible applications of the developed system to the hydroxyl radical detection in atmospheric and chemical dynamics research are discussed.